The Adventures of Sherlock Holmes - Doyle, Arthur Conan, 1859-1930 (Oxford Oxford University Press, 2005)
Hilton Cubitt lives in the country with his American wife. The couple start receiving drawings of little dancing men. Cubitt goes to see Sherlock Holmes about these drawings, which seem to have frightened Cubitt's wife. Holmes thinks they might be secret messages. Then, there is a murder. Now, Holmes must quickly work out.
Include Color Illustration
Keywords: Holmes, Sherlock -- Private investigators -- Detective and mystery stories, English